2018
DOI: 10.1016/j.jhydrol.2017.09.058
|View full text |Cite
|
Sign up to set email alerts
|

Impact of urbanization on groundwater recharge rates in Dübendorf, Switzerland

Abstract: Groundwater, as the world's most important reserve of available fresh water, is known to be affected by urbanization. Managing this resource in a sustainable way is critical for water resource management. Groundwater recharge rates in urban areas remain however still poorly understood and under-researched and knowledge about these rates and their expected changes under increasing urbanization is therefore of primary importance. This study aims to give insight into urban groundwater recharge by performing water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(84 citation statements)
references
References 54 publications
(63 reference statements)
3
68
0
2
Order By: Relevance
“…Nevertheless, ET sensitivity analysis indicate that increase in urban areas and decrease in forestland can promote R e (PRCC values of −0.1222 and 0.002 for urban and forestland), but these values are not significant. Similar values are found in Minnig, et al [45] and it can most likely explain the R e trend from 1986 to 2013, which increases by 72.29 mm/year.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Nevertheless, ET sensitivity analysis indicate that increase in urban areas and decrease in forestland can promote R e (PRCC values of −0.1222 and 0.002 for urban and forestland), but these values are not significant. Similar values are found in Minnig, et al [45] and it can most likely explain the R e trend from 1986 to 2013, which increases by 72.29 mm/year.…”
Section: Discussionsupporting
confidence: 89%
“…In Oaxaca, this is evident by a resurgence of forests [43,44]. Similar results to Minnig et al [45] can be found, indicating that urban increases and forest decrease can decrease ET and increases the likelihood of R e , but these results are not significant with PRCC values of −0.122 and 0.002, respectively.…”
Section: Sensitivity Analysissupporting
confidence: 80%
See 1 more Smart Citation
“…In addition, some studies in Beijing showed the effects of climate change and urbanization on groundwater recharge [55]. Studies indicated landscape pattern change, due to anthropogenic activities in the process of urbanization, played a major role to groundwater recharge [1,48].…”
Section: The Impacts Of Urbanization On Water Balancementioning
confidence: 99%
“…However, unlike meteorological phenomena, which have a large discontinuity, groundwater acting as an intermediate medium to surface water is relatively slow in moving and is relatively less sensitive to changes in external factors [12]. Human activities and artificial construction can affect the groundwater system (e.g., recharge, flow paths, water quality [13][14][15]); however, if the anthropogenic influence is not significant, the groundwater level (GWL) displays a periodicity, such as daily, seasonal, or annual change [16][17][18][19], in addition, GWLs can also response to longer teleconnections and climate variability at multiannual, decadal, or longer time scales [20]. It experiences long-term trends of several hours to several months, depending on the depth and aquifer characteristics.…”
mentioning
confidence: 99%